On the Stability of Hyers Orthogonality Functional Equations in Non-Archimedean Spaces - Wenhui Xu; Qi Liu; Jinyu Xia (European Journal of Mathematical Analysis)
In this paper, we investigate the stability of specially orthogonally functional equations deriving from additive and quadratic functions 4f(x+y)+4f(x−y)+10f(x)+14f(−x)−3f(y)−3f(−y)=f(2x+y)+f(2x−y) and f(x+y+z/2)+f(x+y−z/2)+f(x−y+z/2)+f(y+z−x/2)=f(x)+f(y)+f(z) where f is a mapping from Abelian group to a non-Archimedean space. By adopting a new method, we have made an attempt to prove the Hyers-Ulam stability in non-Archimedean spaces.